HUBUNGAN KONTROL DIRI DENGAN PERILAKU KONSUMTIF PADA MAHASISWA DI STIKES SANTA ELISABETH MEDAN - Siallagan, Ance M.; Derang, Imelda; Nazara, Piarni Gustin (JURNAL DARMA AGUNG HUSADA; Vol 8 No 1 (2021): APRIL, 2021)
Self control is the ability of individuals to control, control and restrain one's own desires in performing an action, able to manage behaviors according to situations and conditions, and have a high sensitivity both to themselves, others and the surrounding environment. Today's students are often unable to restrain or control themselves, so everything they want must be fulfilled, which can lead to consumptive behavior. The purpose of this study is to identify the relationship of self control with consumptive behavior in students of ners study program at STIKes Santa Elisabeth Medan Year 2020. The design of this study is to use correlational methods with cross sectional approaches. Sampling used probability sampling with the number of 135 people. The results showed high self control 78 people (57.8%) and high consumptive behavior of 39 people (28.9%). The results of the analysis with chi-square statistical test obtained a value of p (value) = 0.001 (p<0.05) which means there is a significant relationship between self control and consumptive behavior in students of study program ners at STIKes Santa Elisabeth Medan. It is expected that students will further improve self-control so that consumptive behavior does not get higher.